2021
DOI: 10.1371/journal.pone.0253925
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing COVID-19 vaccine distribution across the United States using deterministic and stochastic recurrent neural networks

Abstract: Optimizing COVID-19 vaccine distribution can help plan around the limited production and distribution of vaccination, particularly in early stages. One of the main criteria for equitable vaccine distribution is predicting the geographic distribution of active virus at the time of vaccination. This research developed sequence-learning models to predict the behavior of the COVID-19 pandemic across the US, based on previously reported information. For this objective, we used two time-series datasets of confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Unsupervised self-organizing map, recurrent neural network, and Stochastic Mixture Density Network [ 147 ]…”
Section: Resultsmentioning
confidence: 99%
“…Unsupervised self-organizing map, recurrent neural network, and Stochastic Mixture Density Network [ 147 ]…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, using models that apply convolutional neural networks and recurring neural networks, applications can be created to predict vaccination patterns in the future [89]. Deterministic and stochastic recurrent neural networks were used to predict the geographic spreading of the active virus using unsupervised learning methods so as to plan vaccine distribution among the USA, as a case study [90].…”
Section: Applying Deep Learning Algorithms In Healthcarementioning
confidence: 99%
“…The multivariate CNN algorithm outperformed the LSTM in terms of validation accuracy and forecasting consistency. CNN has been suggested for long-term forecasting in the absence of seasonality and periodic patterns in time series datasets [90]. The paper mentioned that DL techniques have a significant impact on early detection of COVID-19 with high accuracy rate.…”
Section: Applying Deep Learning Algorithms In Healthcarementioning
confidence: 99%
“…One of the main criteria for equitable vaccine distribution is predicting the geographic distribution of the active virus at the time of vaccination. In the US, Davahli et al [54] employed a self-organizing map, long short-term memory (LSTM) model, recurrent neural network model, and stochastic mixture density network model to predict the behavior of the COVID-19 pandemic. They concluded that the deterministic LSTM model could predict the geographic spread of active virus with considerable accuracy.…”
Section: Vaccine Resource Managementmentioning
confidence: 99%